2017
DOI: 10.1161/atvbaha.116.307648
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 (Nucleotide Oligomerization Domain–Like Receptor Family, Pyrin Domain Containing 3)–Caspase-1 Inflammasome Degrades Contractile Proteins

Abstract: Objective —Increasing evidence suggests that contractile dysfunction in smooth muscle cells (SMCs) plays a critical role in aortic biomechanical dysfunction and aortic aneurysm and dissection (AAD) development. However, the mechanisms underlying SMC contractile dysfunction in sporadic AAD are poorly understood. In this study, we examined the role of the NLRP3–caspase-1 inflammasome, a key inflammatory cascade, in SMC contractile dysfunction in AAD. Approach and Results —We observed significant SMC contractil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 33 publications
(43 reference statements)
5
68
0
2
Order By: Relevance
“…Caspase-1 is responsible for the protein degradation. Thus AAA, TAA, and AD are attenuated in NLRP3Ϫ/Ϫ or caspase-1Ϫ/Ϫ mice treated with ANG II plus high-fat diet (1158). In addition, in a novel model of TAD induced by ANG II infusion with BAPN pretreatment, neutrophil-derived MMP9 is proposed to contribute to TAD (525).…”
Section: Signal Intermediates Contributing To Taa And/or Tadmentioning
confidence: 98%
“…Caspase-1 is responsible for the protein degradation. Thus AAA, TAA, and AD are attenuated in NLRP3Ϫ/Ϫ or caspase-1Ϫ/Ϫ mice treated with ANG II plus high-fat diet (1158). In addition, in a novel model of TAD induced by ANG II infusion with BAPN pretreatment, neutrophil-derived MMP9 is proposed to contribute to TAD (525).…”
Section: Signal Intermediates Contributing To Taa And/or Tadmentioning
confidence: 98%
“…In addition to inflammatory cell accumulation, markers of inflammasomes are present in plasma and AAA. 3840 Two research groups found that inflammasome activation contributed to AAA in AngII-infused mice. 40,41 …”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…40,122124 In contrast to AngII-induced AAA, TAA induced by AngII is independent of hypercholesterolemia. 125 In addition to AngII-induced TAA, co-infusion of AngII and β-aminopropionitrile also induces TAA in mice.…”
Section: Thoracic Aortic Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, NLRP3 is overexpressed in the aorta of patients with coronary atherosclerosis, and aortic NLRP3 expression is correlated with the severity of coronary artery disease and the atherosclerotic risk factors (32). Recently, the NLRP3‐caspase‐1 inflammasome cascade has been described as promoting the degradation of contractile proteins in smooth muscle cells, which causes aortic contractile dysfunction in a model of aortic aneurysm and dissection (33).…”
Section: Discussionmentioning
confidence: 99%